Some aspects of the combined effect of chlorites and chlorates of various concentrations in drinking water on hematological indicators (Environment & Health, 2025)
Objective: to determine the nature and features of changes in hematological parameters of animals under conditions of chronic combined exposure to chlorites and chlorates in drinking water to substantiate the criteria for hygienic assessment of their adverse effects on the body.Materials and methods: combined effect of different concentrations of chlorаtes and chlorites in drinking water on hematological parameters.Results. It was established that the concentration of chlorates and chlorites in drinking water at the level of 0.2 mg/dm3 does not cause significant changes in the studied hematological parameters in rats, they did not go beyond the limits of fluctuations of the physiological norm. The most pronounced changes were observed in groups of animals that received drinking water with a combined content of chlorites and chlorates in concentrations of 0.7 mg/dm3 and 1.2 mg/dm3. In them, the structure of the leukogram changed due to changes in the absolute number of leukocytes (decrease), lymphocytes (decrease), granulocytes (increase) and monocytes (increase). This may indicate the activation of immune processes and compensatory mechanisms. Thus, taking into account the pronounced monocytosis, we can draw conclusions about the strengthening of the body's reactive abilities as a result of increased cell death due to the influence of chlorites and chlorates. The changes also affected the relative number of lymphocytes — a gradual decrease in the indicator was observed in groups of animals that received a combination of chlorites and chlorates at doses of 0.7 and 1.2 mg/dm3. At a concentration of 1.2 mg/dm3, there is a gradual depletion of compensatory mechanisms and a decrease in the resistance of the immune system to the action of the studied substance. Thus, in the conditions of a chronic experiment, the indicated changes in the leukogram may indicate changes in the regenerative processes of leukocytes in the bone marrow to restore the balance of leukocyte indicators in the peripheral blood and ensure the maintenance of the constancy of the body's homeostasis.Conclusions. It was established that the consumption of drinking water with a chlorite and chlorate content of 0.2 mg/dm3 does not affect the hematological indicators of animals. However, the combination of chlorite and chlorate in doses of 0.7 and 1.2 mg/dm3 negatively affects the hematological indicators of peripheral blood, which are indirect signs of manifestations of biological and toxic effects depending on the concentration and duration. This, in turn, indicates a dose-time dependence of changes in indicators, which may be important for predicting the harmfulness of the long-term impact of the studied substances on the functional state of the body. This is important when substantiating hygienic regulations of the negative effects of exposure to the human body and the environment.
Keywords: drinking water; chlorites; chlorates; combined effect; hematological